2021
DOI: 10.3390/ijerph182010588
|View full text |Cite
|
Sign up to set email alerts
|

The Muscle Strength of the Knee Joint after ACL Reconstruction Depends on the Number and Frequency of Supervised Physiotherapy Visits

Abstract: The aim of this study in anterior cruciate ligament reconstruction (ACLR) patients was to assess the effect of six months of supervised physiotherapy with a higher number of visits (SPHNV) compared to supervised physiotherapy with a lower number of visits (SPLNV) on the maximal peak torque (PT) and isometric torque (IT) of values obtained for hamstring (H) and quadriceps (Q) muscles of the knee joints under isokinetic and isometric conditions. Hypothesis: SPHNV improves IT and PT more than SPLNV. Group I had A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 50 publications
0
16
1
1
Order By: Relevance
“…In the study group, five subjects injured their dominant knee and five injured the non-dominant leg. There were no significant differences in age, body height, body weight, thigh circumference, initial knee range of motion and the level of daily physical activity (Tegner Activity Scale) [ 29 , 36 ] between the study group (before PCL injury) and the post-PCL reconstruction group (before test). After the end of 12 weeks training, the subjects in the study group declared that they could return to pre-injury physical activity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the study group, five subjects injured their dominant knee and five injured the non-dominant leg. There were no significant differences in age, body height, body weight, thigh circumference, initial knee range of motion and the level of daily physical activity (Tegner Activity Scale) [ 29 , 36 ] between the study group (before PCL injury) and the post-PCL reconstruction group (before test). After the end of 12 weeks training, the subjects in the study group declared that they could return to pre-injury physical activity.…”
Section: Resultsmentioning
confidence: 99%
“…The rehabilitation effect on the improvement of knee muscle strength between the injured knee and uninvolved knee to decrease leg asymmetry in patients with knee cruciate ligament injury is another concern [ 34 , 36 , 46 ]. Czamara et al [ 36 ] introduced a study to investigate the effect of the number and frequency of supervised physiotherapy visits on the knee muscle strength in patients after anterior cruciate ligament reconstruction (ACLR). They found that a lower number of visits in the ACLR group presented lower values of knee muscle strength in the operated leg compared to the uninvolved leg.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, studies have focused on the assessment of the correlation between the time and number of supervised 6 month physiotherapy protocols with more visits (x = 74) that have been reported compared with supervised physiotherapy with fewer visits (x = 32) [54]. The results indicate a favorable effect of supervised physiotherapy with more visits on the reduction in the differences in relative vertical ground reaction force values and LSI of vertical ground reaction force values between the operated and the uninvolved leg, compared with the values obtained in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…With reference to the previously mentioned results from patients after ACLR [22,54,55], supervised postoperative physiotherapy should be carried out within a longer postoperative period, which requires scientific evidence and, thus, further research.…”
Section: Discussionmentioning
confidence: 99%